Percepções de cooperados e não cooperados em relação às dimensões da sustentabilidade de uma cooperativa leiteira da agricultura familiar - Tiozo, Evandro (2020)
The present study aimed to investigate whether the fact of being part of a cooperative influences the dimensions of sustainability of a dairy family farming business. The research sample consisted of 102 family farmers, 51 of whom are members of a solidarity economy dairy cooperative, located in the São Francisco Resettlement in the city of Cascavel - PR, and 51 are non-members. Literature provided support for the elaboration of fifteen research hypotheses, five for each dimension of sustainability, namely, the economic, social and environmental dimensions. The method adopted for the study was quantitative, with the application of questionnaires, which were elaborated by the author himself based on the studied theories. The data was analyzed by Structural Equation Modeling, and regressions were carried out with the “Partial Least Squares” method in SmartPLS® 3.0 software. The first step consisted in validation of the constructs after which the hypothesis test was performed. As main results of the study, it was found that the cooperative has a positive influence on the sustainability of its members, since the perceptions of the members were positive and statistically significant when compared with the opinions of the non-members. This demonstrated that being part of a cooperative positively impacts the relationship between cooperative and family agriculture. In regard to the economic dimension, the cooperative contributes with aspects related to purchase and marketing and by assisting in productive issues, thus impacting the income of members. In the social dimension, the cooperative collaborates with the involvement of cooperative members, by empowering them with knowledge and enabling them to carry out marketing in a fair and correct manner. As for the environmental dimension, the main contributions related to encouraging and guiding members towards environmentally correct production processes, as well by making changes in their motivations for actions aiming environmental preservation. As a conclusion, it is clear that the cooperative positively influences sustainability dimensions of family farming members, thus demonstrating the importance for their businesses of being part of such an initiative.